The Public Stigma of Birth Mothers of Children with Fetal Alcohol Spectrum Disorders. (24th April 2017) - Corrigan, Patrick W.; Lara, Juana Lorena; Shah, Binoy Biren; Mitchell, Kathleen T.; Simmes, Diana; Jones, Kenneth L.
Abstract : Background: Stigma affects not only the person with a stigmatizing condition such as fetal alcohol spectrum disorders (FASD), but also their family members. This study examined whether there are stigmatizing attitudes about biological mothers of children with FASD in a crowdsourced sample. Methods: Three hundred and eighty‐nine participants were asked to rate levels of difference, disdain, and responsibility on 4 conditions: serious mental illness (MI), substance use disorder (SUD), jail experience, and FASD. A budget allocation task was administered as a proxy of discrimination. Prior experience with each of the 4 conditions was noted to assess familiarity. Results: Research participants viewed mothers of children with FASD as more different, disdained, and responsible than women with serious MI, SUD, and jail experience. Budget allocation toward FASD service programs was significantly lower than that toward all other human service programs. Familiarity with the 3 comparison conditions moderated most of the stigma ratings, but this effect was not seen in the FASD condition. Conclusions: Results supported the notion that mothers of children with FASD are highly stigmatized for their past behavior. The data also suggested that the public might discriminate against this population. Stigma reduction interventions should focus on contact‐based strategies, rather than education‐based strategies. Abstract : We examined whether there are stigmatizing attitudes about biological mothers of children with FASD in a crowdsourced sample. Data showed that participants viewed mothers of children with FASD as more different, disdained, and responsible than women with SMI, SUD and jail experience. Results supported the notion that mothers of children with FASD are highly stigmatized for their past behavior. It also suggested that the public might discriminate against this population.